2005
DOI: 10.1109/tcsi.2005.849134
|View full text |Cite
|
Sign up to set email alerts
|

Description of limit cycles in sigma-delta modulators

Abstract: Abstract-A mathematical framework, based on state-space modeling, for the description of limit cycles (LCs) of 1-bit sigma-delta modulators (SDMs) is presented. It is proved that periodicity in bit output pattern of the SDM implies a periodic orbit in state-space variables. While the state-space description is generally applicable for periodic inputs, the focus is on dc inputs, since this represents the most relevant practical condition. An outcome of the analysis is that, in general, for an th-order SDM, at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 8 publications
(17 reference statements)
0
30
0
Order By: Relevance
“…One technique is to model the quantizer as a threshold function in the state equations, which gets complicated for higher-order Δ-Σ modulators and is limited to 1 st -and 2 nd -order Δ-Σ modulators [1]. Another approach to simplify the analysis has been to assume a DC input to the Δ-Σ modulator [2]- [7]. In [8], separate signal and quantization noise nonlinear gains have been used for the stability analysis of 2 nd -and 3 rd -order Δ-Σ modulators for DC and sinusoidal inputs using the root locus approach.…”
Section: A Literature Review-limitations Of Existing Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…One technique is to model the quantizer as a threshold function in the state equations, which gets complicated for higher-order Δ-Σ modulators and is limited to 1 st -and 2 nd -order Δ-Σ modulators [1]. Another approach to simplify the analysis has been to assume a DC input to the Δ-Σ modulator [2]- [7]. In [8], separate signal and quantization noise nonlinear gains have been used for the stability analysis of 2 nd -and 3 rd -order Δ-Σ modulators for DC and sinusoidal inputs using the root locus approach.…”
Section: A Literature Review-limitations Of Existing Approachesmentioning
confidence: 99%
“…It can be observed that all Jaswinder Lota, Senior Member, IEEE, M. Al-Janabi, Member, IEEE and Izzet Kale, Member, IEEE Nonlinear stability prediction of multi-bit deltasigma modulators for sinusoidal inputs the reported approaches, to the authors' best knowledge, relate to the stability of one-bit ∆-Σ modulators. Furthermore, some of these approaches assume DC inputs and/or are restricted to lower-order ∆-Σ modulators [1]- [7], [10].…”
Section: A Literature Review-limitations Of Existing Approachesmentioning
confidence: 99%
“…The architectures of EFMs decide the sequence length of DDSMs. Since a short sequence length results in unwanted frequency components in the output frequency spectrum [1], much research has been done into maximising the sequence length. There are two approaches to lengthen the sequence length: stochastic and deterministic methods.…”
Section: Introductionmentioning
confidence: 99%
“…This enables to carry out an exhaustive search for cyclic sequences up to a length of 40 clock periods. In [8], [9] authors use state space approach and present a mathematical framework for the description of limit cycles in 1-bit Σ∆ modulators for constant inputs.…”
Section: Introductionmentioning
confidence: 99%